2020
DOI: 10.1177/2192568220979666
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of Lumbar Muscle Performance Between Minimally-Invasive and Open Lumbar Fusion Surgery at 1-Year Follow-Up

Abstract: Study Design: Prospective study. Objective: Minimally-invasive lumbar fusion surgery (MIS) is a viable alternative to conventional open surgery (COS) for spinal disorders. Although MIS seems to be associated with less para-spinal muscle trauma, the actual back muscle performance after MIS and COS remain controversial. This study investigated post-operative para-spinal muscle performance, and the correlation between muscle dysfunction and clinical outcome. Methods: In this prospective, non-randomized control st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Overall, the results of the current study are consistent with ndings reported by Liu et al 10 . Growing literature suggests that the fusion rate of the intervertebral cage may affect the clinical outcomes of patients [28][29][30][31] . The present study found no signi cant difference in the fusion rate between the two surgical methods at the one-year postoperative follow-up, suggesting that both techniques can achieve the expected fusion results(Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the results of the current study are consistent with ndings reported by Liu et al 10 . Growing literature suggests that the fusion rate of the intervertebral cage may affect the clinical outcomes of patients [28][29][30][31] . The present study found no signi cant difference in the fusion rate between the two surgical methods at the one-year postoperative follow-up, suggesting that both techniques can achieve the expected fusion results(Fig.…”
Section: Discussionmentioning
confidence: 99%